Development and validation of a primary sclerosing cholangitis–specific patient‐reported outcomes instrument: The PSC PRO. Issue 1 (10th May 2018) - Younossi, Zobair M.; Afendy, Arian; Stepanova, Maria; Racila, Andrei; Nader, Fatema; Gomel, Rachel; Safer, Ricky; Lenderking, William R.; Skalicky, Anne; Kleinman, Leah; Myers, Robert P.; Subramanian, G. Mani; et al.
Abstract : Primary sclerosing cholangitis (PSC) is a chronic liver disease associated with inflammation and biliary fibrosis that leads to cholangitis, cirrhosis, and impaired quality of life. Our objective was to develop and validate a PSC‐specific patient‐reported outcome (PRO) instrument. We developed a 42‐item PSC PRO instrument that contains two modules (Symptoms and Impact of Symptoms) and conducted an external validation. Reliability and validity were evaluated using clinical data and a battery of other validated instruments. Test‐retest reliability was assessed in a subgroup of patients who repeated the PSC PRO after the first administration. One hundred two PSC subjects (44 ± 13 years; 32% male, 74% employed, 39% with cirrhosis, 14% with a history of decompensated cirrhosis, 38% history of depression, and 68% with inflammatory bowel disease [IBD]) completed PSC PRO and other PRO instruments (Short Form 36 V2 [SF‐36], Chronic Liver Disease Questionnaire [CLDQ], Primary Biliary Cholangitis – 40 [PBC‐40], and five dimensions [5‐D Itch]). PSC PRO demonstrated excellent internal consistency (Cronbach alphas, 0.84‐0.94) and discriminant validity (41 of 42 items had the highest correlations with their own domains). There were good correlations between PSC PRO domains and relevant domains of SF‐36, CLDQ, and PBC‐40 (R = 0.69‐0.90; all P < 0.0001), but lower (R = 0.31‐0.60; P < 0.001) with 5‐D Itch. Construct validity showed that PSC PRO can differentiate patients according to the presence and severity of cirrhosis and history of depression ( P < 0.05), but not by IBD ( P > 0.05). Test‐retest reliability was assessed in 53 subjects who repeated PSC PRO within a median (interquartile range) of 37 (27‐47) days. There was excellent reliability for most domains with intraclass correlations (0.71‐0.88; all P < 0.001). Conclusion: PSC PRO is a self‐administered disease‐specific instrument developed according to U.S. Food and Drug Administration guidelines. This preliminary validation study suggests good psychometric properties. Further validation of the instrument in a larger and more diverse sample of PSC patients is needed. (Hepatology 2018;68:155‐165).